2014
DOI: 10.1007/978-94-017-9487-9_7
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation, Regulation and Function of Th9 Cells

Abstract: Naïve CD4(+) T cells are activated and differentiate to distinct lineages of T helper (Th) cells, which are involved in physiological and pathological processes by obtaining the potential to produce different lineage-specific cytokines that mediate adaptive immunity. In the past decade, our knowledge of Th cells has been significantly expanded with the findings of new lineages. Interleukin (IL)-9 producing T cells are recently identified. In consideration of the ability to preferentially secret IL-9, these cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 92 publications
(175 reference statements)
0
20
0
Order By: Relevance
“…However, it appears that there are different signaling pathways and transcription factors that orchestrate the differentiation of IL-9-expressing CD4 + T cells [12, 13]. After stimulation with PMA plus ionomycin in the presence of BFA, intracellular staining showed that PBMCs from children with allergic asthma expressed higher level of IL-9.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, it appears that there are different signaling pathways and transcription factors that orchestrate the differentiation of IL-9-expressing CD4 + T cells [12, 13]. After stimulation with PMA plus ionomycin in the presence of BFA, intracellular staining showed that PBMCs from children with allergic asthma expressed higher level of IL-9.…”
Section: Resultsmentioning
confidence: 99%
“…IL-9 is a mast cell growth and differentiation factor.IL-9 has been reported to promote IL-4-driven antibody production by B cells, as well as to up-regulate IL-6 production [12, 23]. However, the direct effect of IL-9 on modulating Ig secretion is not well known.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…IL-1β promotes the secretion of cytokines IL-9, IL-10, and IL-21 from T H 9 cells through STAT1-IRF1-dependent mechanisms [22, 90, 91]. Furthermore, this IL-1β-induced T H 9 differentiation increased IL-21, but not IL-9, secretion, and increased IL-21-dependent anti-tumor effects [9294].…”
Section: Th9 Cell Differentiation and Function In Anti-tumor Immunitymentioning
confidence: 99%
“…Our previous animal and human studies have shown that the Treg cells overwhelmed immune response, although no significant alteration was found in terms of Th17 [ 2 , 12 ]. As a new member of CD4 + T cell family, Th9 cells have been known to play a significant role in some diseases, such as allergic diseases and cancers as well as the parasitic infections [ 13 ]. Furthermore, Th9 cells, through the expression of the effector cytokine IL-9, are more efficient than classical Th2 cells at orchestrating antihelminthic responses in helminthic infection in vivo [ 14 ].…”
Section: Discussionmentioning
confidence: 99%